ECTFE membranes produced by non-toxic diluents for organic solvent filtration separation. Issue 84 (26th August 2016) - Ursino, C.; Simone, S.; Donato, L.; Santoro, S.; De Santo, M. P.; Drioli, E.; Di Nicolò, E.; Figoli, A.
Abstract : A new grade of ethylene-chlorotrifluoroethylene, low melting point HALAR® ECTFE (LMP ECTFE), was studied and used as a polymer for the preparation of solvent-resistant flat-sheet membranes. Abstract : A new grade of ethylene-chlorotrifluoroethylene, low melting point HALAR® ECTFE (LMP ECTFE), was studied and used as a polymer for the preparation of solvent-resistant flat-sheet membranes. Among the different types of non-toxic solvents tested, di-ethyl adipate (DEA) was selected for preparing flat sheet membranes via thermally induced phase separation (TIPS). The morphology of the membranes has been analyzed by scanning electron microscopy (SEM) and atomic force microscopy (AFM). Dense and porous membranes have been obtained and characterized by contact angle, pore size and porosity tests. Porous membranes showed an asymmetric structure made of a denser top-side and a spherulitic porous structure on the bottom side. Membrane resistance was studied using the dense membrane in contact with most aggressive organic solvents, such as polar protic, polar aprotic and non-polar solvents. The results suggest that the newly developed LMP ECTFE membranes are very promising candidates for organic solvent separation. Ultrafiltration (UF) and nanofiltration (NF) tests with alcohols and di-methyl formamide (DMF) demonstrated their solvent separation potential.